Improved Hole-Transporting Property via HAT-CN for Perovskite Solar Cells without Lithium Salts - Ma, Yingzhuang; Chung, Yao-Hsien; Zheng, Lingling; Zhang, Danfei; Xiao Yu; Xiao, Lixin; Chen, Zhijian; Wang, Shufeng; Qu, Bo; Qihuang Gong; Zou, Dechun (ACS APPLIED MATERIALS & INTERFACES, 2015)
A nonadditive hole-transporting material (HTM) of a triphenylamine derivative of N,N'-di(3-methylphenyl)-N,N'-diphenyl-4,4'-diaminobiphenyl (TPD) is used for the organic-inorganic hybrid perovskite solar cells. The power conversion efficiency (PCE) can be significantly enhanced by inserting a thin layer of 1,4,5,8,9,11-hexaazatriphenylenehexacarbonitrile (HAT-CN) without adding an ion additive because the hole-transporting properties improve. The short-circuit current density (J(sc)) increases from 8.5 to 13.1 mA/cm(2), the open-circuit voltage (V-oc) increases from 0.84 to 0.92 V, and the fill-factor (FF) increases from 0.45 to 0.59, which corresponds to the increase in PCE from 3.2% to 7.1%. Moreover, the PCE decreases by only 10% after approximately 1000 h without encapsulation, which suggests an alternative method to improve the stability of perovskite solar cells.